AUTOMATED SENTIMENT ANALYSYS EVALUATION OF SOCIAL NETWORK USERS BASED ON FUZZY LOGIC - Elena E. Luneva; Alexandr A. Yefremov; Pavel I. Banokin (Статистика и экономика)
In the article the method of automated sentiment analysisevaluation of social network users is represented. The advantage of suggested method consists in ability taking into accountuser’s authority as well as the fact of several messages from one user. As input data for the sentiment analysis with respect to a certain topic is its relevant messages. Automated analysisof these messages is obtained with application of fuzzy logicalgorithms. Particularly when in messages contains fuzzyhedges. The paper presents experimental data showing the steps of calculation of the resulting sentiment evaluation ofmessages on a certain topic.